The Trans-Pacific Partnership (TPP) in Latin American Regional Outlook - Giuseppe, (Revista Española de Desarrollo y Cooperación, 2023)
Latin America is passing through this phase amid a political and economic turmoil that is weakening the progressive governments and regional schemes that have been driven over the past 15 years, a stage that has been called post-hegemonic regionalism or postneoliberal regionalism. In this sense, on a regional framework where ALBA-TCP, UNASUR, CELAC and MERCOSUR seem not to have enough strength that characterized them on what many authors called Latin American Post-Neoliberalism, the Trans-Pacific Partnership (TPP) strongly arises into the region, making tremble “the incipient regional autonomy”. This paper aims to highlight the main characteristics of the mentioned partnership, in order to make a deep thinking about the future of the Latin American regional areas, more and more disputed not only by regional leaderships but also by the presence of external actors.
Keywords: Trans Pacific Partnership (TPP); Regional Integration; Latin America; Crisis